Repeatability of Vicon Motion Analysis System for upper limb kinematic measurement during fencing lunge action - Chung, W. M.; Yeung, S.; Pak, C. H.; Lee, R. (Hong Kong Physiotherapy Journal, 2011)
Three-dimensional (3D) kinematic motion analysis systems are widely used for clinical decision-making and evaluation of the therapeutic outcome. The objectives of this study were: (1) to assess the 3D upper limb kinematics during the fencing lunge in the able-bodied foil fencers and (2) to evaluate the within- and between-session repeatability of the VICON system. Methods: Three male, right-handed, healthy foil fencers (age 25 3.2 yr; body height 178 5 cm; fencing experience 7 2 yr) participated in this study. A test-retest design was used in which the subjects in sitting repeated five fencing lunge action during two sessions within a 24-hr period. The right upper limb anatomical movement patterns were recorded by VICON. The within- and between-session repeatability of kinematic waveforms of specific anatomical joint angles were evaluated by the coefficient of multiple correlations (CMCs). Results: The results demonstrated moderate to high repeatability of VICON for high-speed upper limb movement pattern of elite fencers during lunge action. The within- and between-session repeatability of shoulder, elbow and wrist kinematic waveforms were moderate to high: the within-session CMCs ranged from 0.70 to 1.00, whereas, between-session CMCs ranged from 0.68 to 0.99. Conclusion: The data recorded from VICON demonstrated moderate to high repeatability in both within- and between-session measurements which supported the potential value of VICON in analyzing and monitoring prospective changes in upper limb movement of individuals after injury, rehabilitation or training.